Impact of the COVID-19 Pandemic on the Lifestyles and Quality of Life of Women With Fertility Problems: A Cross-Sectional Study - Biviá-Roig, Gemma; Boldó-Roda, Ana; Blasco-Sanz, Ruth; Serrano-Raya, Lola; DelaFuente-Díez, Elena; Múzquiz-Barberá, Pedro; Lisón, Juan Francisco (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic has implied worldwide the imposition of confinement measures and mobility restrictions, to a greater or lesser extent. It has also meant the closure of some public medical services such as reproductive care. This situation may have impacted the health-related behaviour and quality of life of women with fertility problems. Objective: The objective of this study was to analyse the effects of confinement and the suspension of reproductive medical care on the lifestyle (diet, physical exercise, and smoking habits), anxiety and depression, and quality of life of infertile women by comparing their pre- and post-confinement situations. Methods: We carried out a cross-sectional, internet-based study. Information was collected on these women's adherence to the Mediterranean diet (MEDAS questionnaire), physical exercise (IPAQ-SF), anxiety and depression (HADS), and quality of life related to fertility (FertiQol) before, during, and after confinement. The survey was conducted between 1 September and 28 October 2020. Results: A total of 85 women participated. There had been a significant increase in anxiety and depression levels (P < 0.001) and an increase in tobacco consumption among female smokers during confinement vs. pre-confinement (62.5% had increased their consumption). The participants had also increased the mean number of hours they spent sitting (P < 0.001). There had also been an increase in vigorous and moderate exercise levels by 40 and 30%, respectively (P = 0.004). However, no differences were observed in these patients' eating habits as a result of confinement (P = 0.416). When the reproduction service was resumed, the participants showed higher anxiety level scores (P = 0.001) with respect to the pre-confinement situation as well as lower mean FertiQol scale score (P = 0.008). Conclusions: Confinement had increased anxiety and depression levels among these infertile women as well as tobacco use among the participants who were smokers. The prolonged closure of reproductive care units decreased the quality of life of the participants of this study. These results suggest the need to implement online programs to improve healthy habits and quality of life of this population group.